Analysis of acid-base misconceptions using modified certainty of response index (CRI) and diagnostic interview for different student levels cognitive - Satya Sadhu; Maria Tensiana Tima; Vika Puji Cahyani; Antonia Fransiska Laka; Desfi Annisa; Atina Rizanatul Fahriyah (Universitas Sebelas Maret, 2017)
The authors in this paper draw attention to the importance of an instrument that can analyze student’s misconception.This study described the kind of the misconception in acid-base theory, and the percentage students’ misconception occur in every subconcept of acid-base theory. The design of this study is a descriptive method, involved 148 of 11th grade science students from Senior High School, which divided into two classes are high cognitive and low cognitive. Further analysis of using Modified Certainty of Response Index (CRI) as a diagnostic instrument is used to explore misconception which in that test included evaluating only content knowledge with considering the reason behind the students' choice of response and their certainty of response in every question. The result of data analysis has shown that misconception occurred in high cognitive class, gained 43,86% and misconception occurred in low cognitive class, gained 24,63%. Based on the diagnostic interview has shown that misconception occurred in students due to students does not understand the concept well and they related the one concept to the other concepts with partial understanding, the result students make the failed conclusions. The type of misconception occurred is a conceptual misunderstanding. According to the data analysis showed that Modified Certainty of Response Index (CRI) is effective used to analyze students’ misconceptions and the diagnostic interview is effective used to know the reasons that caused students which having misconceptions.